2002
DOI: 10.1021/ja026209p
|View full text |Cite
|
Sign up to set email alerts
|

Electron and Mass Transport in Hybrid Redox Polyether Melts Contacted with Carbon Dioxide

Abstract: Films of neat metal salts with covalently attached oligoether side chains ([Co(bpy(CO(2)MePEG-350)(2))(3)](ClO(4))(2); bpy is 2,2'-bipyridine, and MePEG-350 is methyl-terminated oligomeric ethylene oxide with an average molecular weight of 350 Da) undergo marked changes in physical and electrochemical properties upon contact with CO(2). Electrochemical measurements indicate that the physical diffusion coefficient (D(PHYS)) of the Co(II) species, the observed rate constant for Co(II/I) self-exchange (k(EX)), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
47
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(52 citation statements)
references
References 72 publications
4
47
1
Order By: Relevance
“…Ultimately, the results extend our understanding of these materials in regard to possible use in molecular electronic environments that incorporate nucleic acid sequence programming. The present results are consistent with recent results 10 on CO 2 -plasticized Co complex melts, and with the notion that immobilization of counterions can produce a large impediment to electron transfer. 11…”
supporting
confidence: 93%
“…Ultimately, the results extend our understanding of these materials in regard to possible use in molecular electronic environments that incorporate nucleic acid sequence programming. The present results are consistent with recent results 10 on CO 2 -plasticized Co complex melts, and with the notion that immobilization of counterions can produce a large impediment to electron transfer. 11…”
supporting
confidence: 93%
“…It is additionally possible that ionic atmosphere relaxation phenomena influence the DNA electron hopping rate. We have shown that ionic atmosphere relaxation can dominate electron-transfer rates in semisolid media; ,, such control in the present case would mean that the k EX results above are lower limits of the intrinsic electron-transfer rate. Measurements given below show, however, that the physical diffusion of dilute, nontailed metal complexes in a 1:3 (mole ratio) Ni 350 DNA + Ni 350 (ClO 4 ) 2 melt at 67 °C is about 10 -8 cm 2 /s.…”
Section: Resultsmentioning
confidence: 56%
“…[49][50][51][52] In this work, we will demonstrate how the PFIL-modified electrode assembly can be used in flow injection analysis (FIA) in supporting electrolyte-free solutions. [37][38][39][40][41][42][43] The structure of a detection cell for the flow system was shown in Scheme 2(B). Fig.…”
Section: Application In Amperometric Flow Analysismentioning
confidence: 99%
“…Similar results have been obtained with some other ionexchange membranes employed in electrochemical flow systems any added supporting electrolyte. [37][38][39][40][41][42][43] The advantage of our approach is that we do not need any internal electrolyte in the flow cell construction. Another advantage in our system is that the PFIL film has good dissolving properties for many analytes.…”
Section: Application In Amperometric Flow Analysismentioning
confidence: 99%
See 1 more Smart Citation